The B & B approach: Ball-milling conjugation of dextran with phenylboronic acid (PBA)-functionalized BODIPY - Andreozzi, Patrizia; Tamberi, Lorenza; Tasca, Elisamaria; Giacomazzo, Gina Elena; Martinez, Marta; Severi, Mirko; Marradi, Marco; Cicchi, Stefano; Moya, Sergio; Biagiotti, Giacomo; Richichi, Barbara (Beilstein Journal of Organic Chemistry, 2020)
Mechanochemistry is an emerging and reliable alternative to conventional solution (batch) synthesis of complex molecules under green and solvent-free conditions. In this regard, we report here on the conjugation of a dextran polysaccharide with a fluorescent probe, a phenylboronic acid (PBA)-functionalized boron dipyrromethene (BODIPY) applying the ball milling approach. The ball milling formation of boron esters between PBA BODIPY and dextran proved to be more efficient in terms of reaction time, amount of reactants, and labelling degree compared to the corresponding solution-based synthetic route. PBA-BODIPY dextran assembles into nanoparticles of around 200 nm by hydrophobic interactions. The resulting PBA-BODIPY dextran nanoparticles retain an apolar interior as proved by pyrene fluorescence, suitable for the encapsulation of hydrophobic drugs with high biocompatibility while remaining fluorescent.
Keywords: ball milling; boronic ester; dextran; bodipy; nanoparticles